Perbedaan Daya AntibakteriEkstrak Kulit Kokoa (Theobroma cacao)dan NaOCl 2,5% terhadapPorphyromonas gingivalis - Tamara Yuanita; Rifatul Jannah; Edhie Arif Pasetyo; Setyabudi Setyabudi (Universitas Airlangga, 2018)
Background: Since pulp infection plays an important role in the development of periradicular lesions, endodontic treatment should be directed to eliminate bacterial and theirproducts. However, currently 20% of cases of apical periodontitis are not resolved after root canal treatment and therefore required for new root canal disinfection. The most commonly used irrigation material today is NaOCl 2.5%. However, NaOCl has negative effects, including being toxic when the material is injected into the periradicular tissue causing extensive pain, bleeding and swelling. Until now, many drugs come from plants that are still produced from plant extracts. One of the plants that can be utilized is cocoa (Theobroma cacao). Cocoa contains active compounds, such as saponins, tannins, alkaloids, flanonoids, aromatic terpenoids, theobromins and other metabolites. Cocoa husk has been studied to have an antibacterial effect on Porphyromonas gingivalis which is the main bacterial cause of apical periodontal. However, the difference in antibacterial activity between cocoa husk extract and NaOCl 2.5% againstPorphyromonas gingivalis has not been studied. Porpuse:The aim of this study is to compare antibacterial activity of cocoa husk extract and NaOCl 2.5% againstPorphyromonas gingivalis.Method: This research was a laboratory experimental study. Porphyromonas gingivalis were swabbed to nutrient agar medium. Consequently, cocoa husk extract 25% and NaOCl 2.5% were placed in wells of 5mm diameter and nutrient agar medium. The diameter of the zone of inhibition around the test materials was measured after 24 hours.Result:Cocoa husk extract has lower mean inhibitory zone diameter (14.22) than NaOCl 2.5% (16.06). Conclusion:Cocoa husk extract has lower antibacterial activity against Porphyromonas gingivalis compared to NaOCl 2.5%.